Oxygen Containing Groups Modified Phosphate Rock for Pb(II) Adsorption - Shi-Yu Dong; Yang-Hao Zhao; Imran Muhammad; Gul Mehtab; Tie-Zhen Ren (Water, Air, & Soil Pollution, 2026)

Correlation of tree stem diameter with root architecture, mechanical properties, and slope stability in a mountainous Cryptomeria plantation - Mehtab Alam; Jianfeng Chen; Usama Ayub; Umar Muhammad (Journal of Mountain Science, 2026)

Sustainable slope stabilization: root-induced stiffness and damping control in sandy soils under cyclic loading - Ismail Shah; Yuan-Jun Jiang; Mehtab Alam; Xia Xin; Muhammad Mudassar Rehman (CATENA, 2025)

Enhancing Soybean Yields Through Bioinoculants and Topographic Position Site-Specific Management Strategies - Mehtab Muhammad Aslam; Gurbir Singh; Kelly A. Nelson; Gurpreet Kaur (International Journal of Plant Production, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

Prediction of compressive strength of stone dust-based fly ash bricks: experimental study and advanced machine learning algorithm - Mehtab Alam; Adil Khan; Muhammad Umar; Tauqir Ahmed; Ahmad Yar Mazari; Muhammad Usman Arshad (Innovative Infrastructure Solutions, 2025)

Deciphering the complex roles of leucine-rich repeat receptor kinases (LRR-RKs) in plant signal transduction - Ting Tang; Ferdinand Ndikuryayo; Xue-Yan Gong; Elaheh Amirinezhadfard; Mehtab Muhammad Aslam; Mo-Xian Chen; Wen-Chao Yang (Plant Science, 2025)

A review on supercapacitors: Development trends, challenges, and future perspectives - Iqbal Singh; Rohit Sharma; Amardeep kaur; Dinesh Pathak; Anupinder Singh; Muhammad Hamza; Mehtab Singh; Ajay Vasishth (Next Research, 2025)

The regulatory role of phytohormones in plant drought tolerance - Zhenqi Liao; Beibei Chen; Hatem Boubakri; Muhammad Farooq; Luis Alejandro Jose Mur; Daisuke Urano; Chee How Teo; Boon Chin Tan; MD Mahadi Hasan; Mehtab Muhammad Aslam; Muhammad Yahya Tahir; Junliang Fan (Planta, 2025)

Site Response Analysis Considering Site-Affects Leading to Seismic Microzonation Map of Lahore - Maham Basharat; Ajwat Mustafa; Muhammad Umar; Mehtab Alam; Umair Ali; Muhammad Irfan (Geotechnical and Geological Engineering, 2024)

Predicting Standard Penetration Test N-value from Cone Penetration Test Data Using Gene Expression Programming - Mehtab Alam; Jianfeng Chen; Muhammad Umar; Faheem Ullah; Muhammad Shahkar (Geotechnical and Geological Engineering, 2024)

Foliar architecture differentially restrains metal sequestration capacity in wheat grains (Triticum aestivum L.) grown in hyper-chloride-contaminated soils - Muhammad Sajid Aqeel Ahmad; Mansoor Hameed; Muhammad Kaleem; Sana Fatima; Farooq Ahmad; Muhammad Farooq; Mehtab Maratib; Iqra Aziz (Environmental Science and Pollution Research, 2023)

Real-time selective pesticide detection using catalytic behavior of zwitterionic conjugated polymer - Arvin Sain Tanwar; Muhammad Mehtab; Jin-Tae Kim; Kwang-Joong Oh; Parameswar Krishnan Iyer; Yeon-Ho Im (Chemical Engineering Journal, 2023)

GRAS transcription factors emerging regulator in plants growth, development, and multiple stresses - Muhammad Waseem; Oswald Nkurikiyimfura; Sylvain Niyitanga; Bello Hassan Jakada; Iffat Shaheen; Mehtab Muhammad Aslam (Molecular Biology Reports, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Tomato COI gene family identification and expression under abiotic and phytohormone stress - Muhammad Waseem; Mehtab Muhammad Aslam; Iffat Shaheen (Journal of Genetics, 2021)

Salivary Proteomic Analysis of Betel Nut (Areca catechu) Consumers by Mass Spectrometry Revealed Primary Indication of Oral Malignancies - Rabia Sultan; Munazza Raza Mirza; Muhammad Iqbal Choudhary; Mehtab Alam; Ikram-ul Haque (International Journal of Peptide Research and Therapeutics, 2020)

Detection of QTLs for outcrossing-related traits in rice (Oryza sativa L.) by association mapping and the RSTEP-LRT method - Lal Bux; Dalu Li; Muhammad Faheem; Ognigamal Sowadan; Zhiyao Dong; Erbao Liu; Mehtab Ali; Yanhui Li; Helder Manuel Sitoe; Abdul Aziz Mirani; Delin Hong (Euphytica, 2019)

Different ambient management intervention techniques and their effect on milk production and physiological parameters of lactating NiliRavi buffaloes during hot dry summer of subtropical region - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Rahman Ullah; Qurat ul Ain; Muhammad Sajid Hasni; Mahboob Ali; Abdul Rashid; Imran Qaisar; Ghazunfar Rashid; Rafi Uddin (Tropical Animal Health and Production, 2019)

Effect of ambient management interventions on the production and physiological performance of lactating Sahiwal cattle during hot dry summer - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Khalid Javed; Mehboob Ali; Ghazanfar Rashid; Rafi Uddin; Ali Hassan Badini; Mudassar Jehan (Tropical Animal Health and Production, 2018)

Natural Dietary Supplementation of Anthocyanins via PI3K/Akt/Nrf2/HO-1 Pathways Mitigate Oxidative Stress, Neurodegeneration, and Memory Impairment in a Mouse Model of Alzheimer’s Disease - Tahir Ali; Taehyun Kim; Shafiq Ur Rehman; Muhammad Sohail Khan; Faiz Ul Amin; Mehtab Khan; Muhammad Ikram; Myeong Ok Kim (Molecular Neurobiology, 2018)